2019
DOI: 10.1038/s41598-019-56329-7
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 partial deletion induces synaptic plasticity deficit in adult mice

Abstract: BACE1 is the first enzyme involved in APP processing, thus it is a strong therapeutic target candidate for Alzheimer’s disease. The observation of deleterious phenotypes in BACE1 Knock-out (KO) mouse models (germline and conditional) raised some concerns on the safety and tolerability of BACE1 inhibition. Here, we have employed a tamoxifen inducible BACE1 conditional Knock-out (cKO) mouse model to achieve a controlled partial depletion of BACE1 in adult mice. Biochemical and behavioural characterization was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
3
19
3
Order By: Relevance
“…The behavioural effects of BACEi treatment in mice presented here are similar to those reported for a conditional knockout line with BACE1 deletion in postnatal forebrain excitatory neurons (29), namely hyperactivity on the open eld, indicated by greater distance travelled, and no memory impairment in context fear conditioning or in the probe trial of the Morris water maze. Whilst no memory impairment in context fear conditioning was also observed in an adult conditional knockout with partial BACE1 deletion (30), both this study and a previous study of BACE inhibition in mice (19) report no hyperactivity on the open eld. Results from the former are in contrast to our ndings from the 15mg/kg/day BACEi cohort, with both protocols causing an ~ 50% decrease in Aβ40 brain levels in adult mice ((30), Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The behavioural effects of BACEi treatment in mice presented here are similar to those reported for a conditional knockout line with BACE1 deletion in postnatal forebrain excitatory neurons (29), namely hyperactivity on the open eld, indicated by greater distance travelled, and no memory impairment in context fear conditioning or in the probe trial of the Morris water maze. Whilst no memory impairment in context fear conditioning was also observed in an adult conditional knockout with partial BACE1 deletion (30), both this study and a previous study of BACE inhibition in mice (19) report no hyperactivity on the open eld. Results from the former are in contrast to our ndings from the 15mg/kg/day BACEi cohort, with both protocols causing an ~ 50% decrease in Aβ40 brain levels in adult mice ((30), Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…Nevertheless, our results reinforce the need to examine the effect of chronic BACEi treatment on spine density and morphology with particular attention given to mushroom spine types, noting that any spine changes will vary according to neuron and dendrite type. The recently reported hippocampal long-term potentiation de cit in mice with only partial adult BACE1 deletion (30) emphasizes the importance of understanding how synaptic plasticity may be affected in patients treated with BACE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…( 98 ) reported impairment of LTP in CA1 of conditional BACE1-deficient mice, whereas CA1 LTP was reported to be normal in a different BACE1 cKO mouse model ( 99 ). However, we showed that CA1 LTP was impaired in BACE1 cKO mice with a partial reduction of BACE1 (∼50% to ∼70%) ( 100 ). Thus, BACE1-dependent imbalance of PSA-NCAM1 could be the underlying mechanism of the abnormal LTP in CA1 in BACE1−/− and BACE1 cKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the extracellular concentration of Aβ increases after neuronal stimulation [123,253] and interstitial fluid Aβ concentration positively correlates with neuronal activity in human brain [29]. Interestingly, both APP knockout [53] and BACE1 knockout [139,154,272,273] in vivo induce cognitive deficits and impair LTP. Wild-type mice given BACE1 inhibitors also show a dose-dependent suppression of LTP and impaired cognitive performance [74].…”
Section: Physiological Concentrations Of Aβ Enhance Ltpmentioning
confidence: 99%